Improvement of Timeliness of Inpatient Discharge Summary in an Inner-City Urban Community Hospital - I. Elmubarak; R. Akiyode; A. Milad; A. Gardezi; F. Hamada; T. Rai; S. Manwani (Journal of Scientific Innovation in Medicine, 2021)
Background: Discharge summary (DS) plays a central role in transition of care between inpatient and outpatient settings and is a patient safety issue [1, 2]. Baseline data showed that <50% of pediatric inpatient discharge summaries in our hospital are completed within 72 hours of discharge. Objective: To assess and improve timeliness of Discharge summary with goal of ≥80% of inpatient pediatric discharge summaries completed within 72 hours. Methods: We studied the current state through data review to determine the baseline DS completion rates. A quality improvement project was initiated using the PDSA model with 9 consecutive cycles conducted over a 3-year period. After reviewing literature and conducting surveys we adopted several interventions [1, 2, 3]. The primary objective was to improve the percentage of discharge summaries completed within 72 hours from a baseline rate of 35% to ≥80%. Intervention: Guided by the baseline data and results of surveys, we applied the following interventions: We adopted a specific pediatric discharge summary electronic medical record (EMR) template and implemented a hard stop to assign an attending for signature. All pediatric residents were trained on the requirements of DS during intern orientation and protected time has been assigned for orientation of all residents at the beginning of every inpatient rotation. Clear rules were established to assign responsibility of DS completion among residents to avoid miscommunication. A discharge summary logbook was established to follow DS status. Senior residents and chief residents were assigned the role of monitoring. Feedback of DS completion and timeliness was included in the mid-cycle evaluation by the attending. Results: 72-hour completion rates improved from below 50% in cycle 1 to >80% by cycle 7. A steady improvement in the first 3 cycles was followed by a drop in completion rates between cycle 3 and cycle 7, reaching a nadir of 42%. This was attributed to lack of adequate training and assignment of responsibility, and interventions 3 through 5 were applied. Last three cycles showed completion rates >80%. Discussion: Sustained improvement in DS timeliness was evident as illustrated in 'Figure 1'. However, there is still a significant portion of DS which are delayed. Potential causes include weekend coverage by non-floor residents and poor-quality DS that requires modification before attending can sign off the document. Our future PDSA cycles will reinforce current interventions and focus on improving quality of DS using quality report cards and feedback from primary providers.